Prognostic relevance of exercise testing in hypertrophic cardiomyopathy. A systematic review - Rodrigues, Tiago (2021)
© 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).